Renewable energy sources in the development of tourism in the protected areas of Poland: the example of the center of religious tourism in Kodeń - Chodkowska-Miszczuk, Justyna (Studia Ecologiae et Bioethicae, 2016)
The aim of the article is to determine the role of renewable energy sources (RES) in the development of tourism in the areas which are famous for their natural and cultural values (protected areas). The example discussed in the article is the center of religious and pilgrimage tourism in Kodeń (Lubelskie voivodship, bialski poviat). The analyzed tourism center is located in the Bug River Protected Landscape Area and the area of the Natura 2000, the Middle Bug River Valley. It seems very significant to point out: (1) the role of RES in the development of tourism in the areas, which are famous for their natural and cultural values; (2) whether or not the production of energy in small-scale RES installations (up to about 200 kW) improves the quality of tourist services in protected areas and allows the creation of ecological quality of these services and (3) which RES are the most appropriate for use in the tourist facilities located in protected areas.